KEMISKINAN DAN PENGARUHNYA TERHADAP MOTIVASI DAN PRESTASI BELAJAR ANAK-ANAK DI KOTA LANGSA - Basri Ibrahim (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2014)
This research is intended to discuss the influence of poverty toward children learning motivation and explain the relation among motivation toward academic achievement in poor family in Langsa. Quantitative methodbeing applied on this research shows that the influence of poverty towards student academic achievement tends to be solid, so that the students education level are influenced by their family economic background. Moreover this condition will also influence the student learning motivation. Finally, the family with poverty tend to ignore their children education due to their daily needs is more important than thir children education